Impact of sports participation on mortality rates among Brazilian adults - Turi-Lynch, Bruna C. [UNESP]; Monteiro, Henrique Luiz [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Sui, Xuemei; Lemes, Ítalo Ribeiro [UNESP]; Codogno, Jamile Sanches [UNESP] (My University, 2019)
Objective: To analyze the possible dose-response association between components of sports participation (intensity, volume and previous engagement) and 4-year mortality rates among Brazilian adults. Methods: 679 males and females (mean age among men = 66.7 ± 9.3 years old and mean age among women = 64.8 ± 8.9 years old) composed the study sample. Sports participation was assessed using Baecke’s questionnaire, which considers intensity, duration and previous engagement. Medical records were used to identify the cause of the death. Cox regression analysis was performed to determine the independent associations of exercise components and mortality. Results: Participants that reported exercising at moderate-vigorous intensity (Moderate/vigorous: 4.1% versus None/light: 10.3% [p-value = 0.012]; HR = 0.42 [0.1 to 0.94)] and for more than four months (≥4 months: 5.3% versus <4 months: 10.2% [p-value = 0.038]; HR = 0.47 [0.24 to 0.94]) had lower mortality risk. The percentage of survival according to all-cause mortality was significantly higher for participants engaged in sports at moderate-vigorous intensity (p-value = 0.014), as well as for those engaged in sports for periods superior than four months (p-value = 0.036). Conclusion: We found higher percentage of survival among adults engaged in sports at moderate-vigorous intensity and with at least four months of previous engagement.
Keywords: epidemiology; Mortality; public health; sports